PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP MINAT DAN HASIL BELAJAR BIOLOGI PADA SISWA K E LAS XI IPA SMA NEGERI I MANOKWARI - Parinding, Margaretha; Antoh, Alfred A. (Magister Pendidikan IPA, UNCEN, 2015)
The goals of this study are to know the influence of Cooperative Learn in g Model Type Scramble application on student sâ interest in learning Biology and to know the impact of this model application on the learning outcomes of students on the subject of Cell Structure and Function. The study design is a Pre-Experiment al De sign in a